Novel technique to produce hybrid P/M components using dissimilar ferrous alloys - Oh, Min Chul; Seok, Hyunjoo; Jo, Yeongcheol; Ahn, Byungmin (Archives of Metallurgy and Materials, 2019)
The objective of the present research is to develop the novel multi-compaction technology to produce hybrid structure in powder metallurgy (P/M) components using dissimilar Fe-based alloys. Two distinct powder alloys with different compositions were are used in this study: Fe-Cr-Mo-C pre-alloyed powder for high strength and Fe-Cu-C mixed powder for enhanced machinability and lower material cost. Initially, Fe-Cu-C was pre-compacted using a bar-shaped die with lower compaction pressure. The green compact of Fe-Cu-C alloy was inserted into a die residing a half of the die, and another half of the die was filled with the Fe-Cr- Mo-C powder. Then they subsequently underwent re-compaction with higher pressure. The final compact was sintered at 1120°C for 60 min. In order to determine the mechanical behavior, transverse rupture strength (TRS) and Vickers hardness of sintered materials were measured and correlated with density variations. The microstructure was characterized using optical microscope and scanning electron microscope to investigate the interfacial characteristics between dissimilar P/M alloys.
Keywords: Compaction pressure; Diffusion behavior; Interface boundaries; Interfacial characteristics; Mechanical behavior; Powder metallurgy (P/M); Pre-alloyed powder; Transverse rupture strength; Diffusion behavior; Hybrid Fe alloy; Interface boundary; Multi-compaction